(3QSGdI aj GdSjas - (3Ydj LdHj afdj RGOgs
(3ChdgG (B:s
(3GdMeO ddg GdPi Sf HeaQhV Jhajbg Sjha GdCacGQ GdUGFHg hHYO aEf GdSja ai MfGOS GdhbGFY TgGH dGeY hYdi SGFd GdZQGFe HjGf bGWY s
(3BNQgG (B:s
(3GdSja eSdhd hYGed GdQeM Sehc hjQMe Gddg YHOkG bGd BejfG JeJ GdebGeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3GdfSNI HgG MhGTs
(3afhfs
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs